2001
DOI: 10.1023/a:1012526406741
|View full text |Cite
|
Sign up to set email alerts
|

The expression of cytochrome P450 enzymes in human breast tumours and normal breast tissue

Abstract: Environmental chemicals are one of the risk factors in breast cancer genesis. Cytochrome P450 (CYP) enzymes play a major role in the activation of these chemicals. Using highly specific and sensitive reverse transcriptase-polymerase chain reaction (RT-PCR) analysis. the expression profile of all major xenobiotic metabolizing CYP forms was screened in breast tumour and surrounding tumour free (control) breast tissue in a series of 20 sample pairs obtained from females with infiltrating ductal carcinoma. The lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
69
1

Year Published

2006
2006
2016
2016

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 93 publications
(73 citation statements)
references
References 30 publications
3
69
1
Order By: Relevance
“…[40][41][42][43] Studies in our and other laboratories have indicated diverse levels of CYP2E1 gene expression in a manner dependent on the genetic background and the migratory potential of these cells. [16,17,29,34] CYP2E1 overexpression in breast cancer cells is involved in the alteration of numerous pathways linked to the disease such as cell cycle control, apoptosis, autophagy, ER stress and UPR. [29,44,45] In addition to these, another pathway that is regulated by the cellular redox state is cellular energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[40][41][42][43] Studies in our and other laboratories have indicated diverse levels of CYP2E1 gene expression in a manner dependent on the genetic background and the migratory potential of these cells. [16,17,29,34] CYP2E1 overexpression in breast cancer cells is involved in the alteration of numerous pathways linked to the disease such as cell cycle control, apoptosis, autophagy, ER stress and UPR. [29,44,45] In addition to these, another pathway that is regulated by the cellular redox state is cellular energy metabolism.…”
Section: Discussionmentioning
confidence: 99%
“…[13] Apart from the liver CYP2E1 gene expression has been detected in other tissues such as breast, lung, kidney and hematopoietic tissues [13] and has been reported to be over expressed in malignant compared to normal tissues. [14][15][16][17] CYP2E1 overexpression in cancer is attributed to the inflammatory conditions present in the tumor microenvironment characterised by increased inflammatory cytokine production which affects CYP2E1 gene expression. [18][19][20] Several CYP2E1 dependent mechanisms contributing to tumorigenesis have been suggested including formation of toxic intermediate derivatives and activated carcinogens.…”
Section: Introductionmentioning
confidence: 99%
“…8 The CYP3A5*3C allele encoding the truncated CYP3A5 protein is the most common allele in Caucasian populations (up to 95%). 8 CYP1B1 is the most prominent human cytochrome in breast tissue 9 and is often overexpressed in tumor cells. [10][11][12] There is some evidence to suggest that the taxanes paclitaxel and docetaxel are competitive inhibitors of CYP1B1 activity 13 and recent data has identified docetaxel as an effector of CYP1B1.…”
Section: Introductionmentioning
confidence: 99%
“…20 The main organ for CYP expression is the liver, but CYP1A1, 3A4, 3A5, 1B1 and 2E1 were also expressed in nonneoplastic and neoplastic breast tissue on the mRNA expression and protein levels, pointing to a possible local activation of estrogen to potentially carcinogenic metabolites. [21][22][23][24][25] However, as of today, the role of CYP expression in breast tumors is unknown.The GENICA study is a population-based breast cancer casecontrol study for the assessment of environmental and molecular risks in Germany. 26,27 In addition, the study provides a comprehensive series of incident breast tumors suitable for the investigation of tumor-associated factors potentially relevant in breast tumorigenesis and tumor progression.…”
mentioning
confidence: 99%
“…20 The main organ for CYP expression is the liver, but CYP1A1, 3A4, 3A5, 1B1 and 2E1 were also expressed in nonneoplastic and neoplastic breast tissue on the mRNA expression and protein levels, pointing to a possible local activation of estrogen to potentially carcinogenic metabolites. [21][22][23][24][25] However, as of today, the role of CYP expression in breast tumors is unknown.…”
mentioning
confidence: 99%